Pengembangan Web Pembelajaran Dengan Fasilitas Teknologi Video Tayang Tunda pada Mata Kuliah Komputer Grafis - Soepriyanto, Yerry (2011)
Computer Graphics Course is a course that generally in volves a lot of technical experience in the operation of computer application programs. It makes the learning done on a large classis not running optimally. This study aims to produce a web-based media with video delay technology facilities on the course computer graphics. This facility is used to resume a procedure or a technical process to create works of graphic design when face to face in the classroom. The analysis showed that this is avalid web learning to be used as a medium of learning. Keyword: web learning, video delay technology, graphic computer subject